2022
DOI: 10.1186/s40798-022-00462-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Long-Term Exercise Modalities on Tissue Stiffness

Abstract: Stiffness is a fundamental property of living tissues, which may be modified by pathologies or traumatic events but also by nutritional, pharmacological and exercise interventions. This review aimed to understand if specific forms of exercise are able to determine specific forms of tissue stiffness adaptations. A literature search was performed on PubMed, Scopus and Web of Science databases to identify manuscripts addressing adaptations of tissue stiffness as a consequence of long-term exercise. Muscular, conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…In contrast, a review by Thomas et al [101] indicated that the loading of a tendon with RT increases its stiffness by modifying elastic properties versus morphological adaptations such as an increased cross-sectional area. This increase in tendon stiffness was not dependent on muscle contraction type, trained state, or age.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, a review by Thomas et al [101] indicated that the loading of a tendon with RT increases its stiffness by modifying elastic properties versus morphological adaptations such as an increased cross-sectional area. This increase in tendon stiffness was not dependent on muscle contraction type, trained state, or age.…”
Section: Discussionmentioning
confidence: 94%
“…The plateau value for HR depends on the cardiorespiratory fitness of the subjects (those who are less fit have higher values of HR) [17]. On the other hand, it is well known that physically trained subjects have good arterial elasticity and low PWV values [18][19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic stiffness-a biomechanical property of the muscle characterized by resistance to contraction or opposition to an external force deforming its initial shape. In the case of abnormally high stiffness, a more significant effort of the agonist's muscle is required to stretch the stiff antagonist, leading to an inefficient economy of movement [32]. In addition, increased muscle stiffness also creates unfavorable conditions for blood circulation and microcirculation, significantly reducing their ability to exercise.…”
Section: Measurement Of Muscle and Tendon Stiffness And Flexibilitymentioning
confidence: 99%